2007
DOI: 10.1175/jas3918.1
|View full text |Cite
|
Sign up to set email alerts
|

Weather Regime Prediction Using Statistical Learning

Abstract: Two novel statistical methods are applied to the prediction of transitions between weather regimes. The methods are tested using a long, 6000-day simulation of a three-layer, quasigeostrophic (QG3) model on the sphere at T21 resolution.The two methods are the k nearest neighbor classifier and the random forest method. Both methods are widely used in statistical classification and machine learning; they are applied here to forecast the break of a regime and subsequent onset of another one. The QG3 model has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…The existence of such a nongaussian behavior in the observational data sets is still a subject of an ongoing debate (Hsu and Zwiers 2001;Stephenson et al 2004;Deloncle et al 2007). Berner and Branstator (2007) identified significant deviations from gaussianity in a four-dimensional phase space of an atmospheric general circulation model and showed that the corresponding phase-space structure can be described in terms of two off-centered Gaussian distributions.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of such a nongaussian behavior in the observational data sets is still a subject of an ongoing debate (Hsu and Zwiers 2001;Stephenson et al 2004;Deloncle et al 2007). Berner and Branstator (2007) identified significant deviations from gaussianity in a four-dimensional phase space of an atmospheric general circulation model and showed that the corresponding phase-space structure can be described in terms of two off-centered Gaussian distributions.…”
Section: Discussionmentioning
confidence: 99%
“…[24], [25]). A forest is a combination of tree predictors such that each tree depends on a vector of independently and randomly sampled values, or features, with the same distribution for all trees in the forest.…”
Section: B Random Forestmentioning
confidence: 99%
“…A first necessary step in view of a possible empirical application of the energetic argument to real systems, particularly within low-frequency variability of atmospheric patterns, in the same spirit of Kondrashov et al (2004) where a Lorenz model is also used as a test case -and Deloncle et al (2007), is to check whether a given statistical tool working solely on the solutions of the model (i.e., ignoring dynamical laws) is able to capture the relation between predictors and predictands in the system itself.…”
Section: Predictions In Lorenz Systemmentioning
confidence: 99%